Penerapan Manajemen Sarana dan Prasarana di SD Negeri 2 Srikaton Adiluwih - Astuti, Yeni; Ma’arif, Amrulloh Khoirul; Masrur, Moh (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The objective of this study is to determine the execution of the current facilities and infrastructure management at SD N 2 Srikaton Adiluwih. The study methodology employed is qualitative, utilizing a descriptive approach. The research employs a data collection process that involves conducting interviews, making observations, and documenting information. The research and discussion indicate that the management of facilities and infrastructure at SD N 2 Srikaton. This theory encompasses five functions: 1) planning educational infrastructure needs, 2) procuring educational infrastructure, 3) maintaining educational infrastructure, 4) storing educational infrastructure, and 5) supervising educational infrastructure. Facilities and infrastructure management refers to the cooperative practice of optimally and proficiently employing all educational equipment. Managing educational buildings and infrastructure is a component of studying school administration or educational administration, and it is occasionally a responsibility of school principals who serve as school administrators. The administration of facilities and infrastructure at SD N 2 Srikaton Adiluwih has been completed, while there are still a few facilities and infrastructure that have not been provided, such as laboratory buildings and teaching aids.